A vanadium-titanium-niobium composite steel shot, its preparation method and application
By using specific proportions of vanadium, titanium, niobium and other elements in steel balls and combining the use of basalt fibers, the existing steel balls have been solved, and the problems of uneven hardness, fast wear, difficult to balance hardness and toughness, and poor corrosion resistance are achieved. Higher hardness, toughness and corrosion resistance.
Patent Information
- Application Number
- CN202411787859.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The existing steel balls have problems with uneven hardness, fast wear, balance of hardness and toughness, and poor corrosion resistance.
Vanadium-titanium-niobium composite steel balls are used, and the components contain specific proportions of vanadium, titanium, niobium, manganese, silicon, chromium, boron, basalt fibers, iron, etc. The components are fusion uniform and steel are improved through special preparation methods and coolant design. The morphology of the pill is qualified.
It significantly improves the balance of hardness and toughness of steel balls, extends service life, reduces the shooting peening rate and loss rate, and improves corrosion resistance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alloy products, and specifically relates to a vanadium-titanium-niobium composite steel shot and a preparation method and application thereof. Background Art
[0002] Steel shot is an important metal abrasive. It can be widely used in cleaning, strengthening and pretreatment of metal surfaces by using equipment such as shot blasting machines and sand blasting machines. In the shipbuilding industry, steel shot is used to remove rust and old paint layers on the surface of the hull, prepare for the construction of new coatings, improve the adhesion of the coating, and extend the service life of the ship. In steel structure manufacturing, steel shot can clean the welding slag and oxide scale after welding, making the surface of the steel structure smoother and flatter, and enhancing its aesthetics and corrosion resistance. In the field of automobile manufacturing, steel shot can clean and strengthen the surface of automobile parts, and improve the fatigue strength and wear resistance of parts. In addition, steel shot is also used in casting, forging, machining and other industries to clean the molding sand and oxide scale on the surface of castings and forgings, and to remove burrs on the surface of machined parts.
[0003] In order to achieve better treatment effects and improve treatment efficiency, it is necessary for the steel shot to have good morphology, hardness, toughness and wear resistance, as well as to select appropriate steel shot size and injection speed. Higher hardness can ensure that the steel shot can effectively remove impurities and oxide scale on the metal surface during cleaning and strengthening, and will not break easily. Good toughness makes the steel shot not easy to break during use, reduces the loss of steel shot, and improves the recycling efficiency. Higher wear resistance can ensure that its morphology and size do not change significantly during long-term use, and continue to play a cleaning and strengthening role. The cleaning efficiency of steel shot depends on factors such as its size, hardness, and injection speed. Suitable steel shot can clean a large area of metal surface in a shorter time.
[0004] Common steel shot diameters range from 0.2mm to 2.5mm. Steel shots of different sizes are suitable for different application scenarios. Steel shots with smaller diameters are suitable for surface cleaning and strengthening of precision parts, and can remove tiny impurities and burrs without causing excessive damage to the surface of the parts. Steel shots with larger diameters are suitable for large-area, high-strength surface cleaning and strengthening, such as ships, steel structures, etc.
[0005] There are several main methods for preparing steel shots: (1) Atomization method: The molten steel is atomized into fine droplets through a high-pressure atomizer, and the droplets are rapidly cooled and solidified in the air to form steel shots; the steel shots prepared by this method have regular shapes, smooth surfaces, and uniform hardness, but the equipment cost is high, the equipment consumption is large, and the energy consumption is high. (2) Centrifugal method: The molten steel is thrown into steel shots by centrifugal force. The steel shots prepared by the centrifugal method are uniform in size and have high hardness, but the shape is not as regular as the steel shots prepared by the atomization method, and there is a high rate of morphological defects. (3) Wire cutting method: The steel wire is cut into small pieces, and then the small pieces of steel wire are made into steel shots through heating, extrusion and other processes. The steel shots prepared by the wire cutting method are lower in cost, but the quality is relatively worse.
[0006] Existing steel shots are mainly made of high carbon steel or alloy steel, with different composition ratios and preparation processes, and their performance varies greatly. The main problems are uneven hardness, rapid wear, difficulty in balancing hardness and toughness, and poor corrosion resistance.
[0007] (1) Uneven hardness: Due to differences in production processes and fluctuations in the homogeneity of raw materials, there are certain differences in the hardness of steel shots, which may cause excessive wear or breakage during use. This will affect the consistency of the effect of steel shots during surface treatment and strengthening.
[0008] (2) Rapid wear: During high-intensity use, the steel shot itself will also wear, especially when processing materials with higher hardness, the wear rate is faster. This not only increases the cost of use, but also leads to a gradual decline in the treatment effect, and the steel shot needs to be replaced frequently.
[0009] (3) The balance between hardness and toughness: Some high-hardness steel shots provide strong cleaning and strengthening capabilities, but often have relatively insufficient toughness. This causes the steel shots to break easily during use, resulting in excessive particles and dust. The particles not only affect the treatment effect, but also cause damage to the equipment and the workpiece being treated. Although steel shots with lower hardness have better toughness and are not easy to break, their cleaning and strengthening effects are not ideal.
[0010] (4) Poor corrosion resistance: Ordinary steel shots are prone to rust when used in some humid or corrosive environments. Rusted steel shots not only affect the appearance, but also reduce their performance. For example, the surface of rusted steel shots will become rough, causing scratches on the surface of the workpiece being processed; at the same time, the hardness and strength of rusted steel shots will also decrease, affecting the cleaning and strengthening effects.
[0011] The characteristics of steel shot composition, performance, size, specifications and preparation methods determine its applicability in different application scenarios. With the continuous development of industrial technology, the performance and quality requirements of steel shot will continue to increase, and the preparation technology of steel shot also needs to be continuously innovated and improved. Summary of the invention
[0012] The problems of uneven hardness, rapid wear, balancing hardness and toughness, and poor corrosion resistance of steel shots in the prior art are addressed. The present invention provides a vanadium-titanium-niobium composite steel shot and a preparation method and application thereof. The steel shot is a high-carbon alloy steel containing vanadium, titanium, niobium, manganese, silicon, chromium, boron, basalt fiber, iron and other components in specific proportions. A special preparation method is designed to enhance the uniformity of component fusion, a special coolant is designed to improve the qualified rate of steel shot morphology, and basalt fiber is fused to the surface of the steel shot to improve toughness, wear resistance and crack resistance. The combined use of various components can greatly improve the performance and corrosion resistance of high-carbon steel shots, and comprehensively improve hardness and toughness. After shot peening, the steel shots can maintain integrity during cleaning and strengthening, will not break easily, and have a low loss rate. The specific technical scheme is as follows:
[0013] A vanadium-titanium-niobium composite steel shot comprises the following components in percentage by mass: 1.00%-1.50% vanadium, 1.00%-1.50% titanium, 1.50%-2.00% niobium, 1.20%-1.50% manganese, 0.90%-1.30% carbon, 0.50%-1.00% silicon, 0.50%-1.00% chromium, 0.30%-0.60% boron, 0.10%-0.50% basalt fiber, less than 0.05% sulfur, less than 0.05% phosphorus, and the balance is iron.
[0014] In the above technical solution, the density of the steel shot is greater than 7.40g / cm 3 ; The diameter specification of the steel shot is 0.2mm~3.0mm.
[0015] The method for preparing the above-mentioned vanadium-titanium-niobium composite steel shot comprises the following steps:
[0016] S1: Add titanium, manganese, carbon and silicon to molten iron at 1700℃~1900℃ according to mass percentage, mix and smelt evenly to obtain fluid A;
[0017] S2: Mix and melt vanadium, chromium and boron at 2100°C to 2300°C according to mass percentage to obtain fluid B;
[0018] S3: melting niobium at 2500°C to 2800°C according to mass percentage to obtain fluid C;
[0019] S4: fluid A, fluid B and fluid C are transferred into a sealed furnace, heated to 2480°C to 2600°C and stirred evenly, and then cooled to 1600°C to 1800°C to obtain molten steel;
[0020] S5: Use centrifugal atomization granulation equipment to sling the molten steel into small droplets, and throw the small droplets into the coolant, the coolant shapes the small droplets to obtain semi-finished steel shots;
[0021] S6: taking out the semi-finished steel shot, washing, drying and sorting, and then quenching the semi-finished steel shot that has passed the sorting, heating it to 900°C to 1000°C, keeping it warm for 20min to 30min, and then water cooling it to obtain quenched steel shot;
[0022] S7: Temper the quenched steel shot, keep it at 400℃~500℃ for 50min~80min, cool it down, and finely screen the particle size to obtain finished steel shot with consistent size specifications.
[0023] In S1 of the above preparation method, the molten iron is molten iron obtained by smelting and removing impurities from iron ore, and the molten iron contains impurities of sulfur <0.05% and phosphorus <0.05%; the carbon is graphite powder, and the particle size of the graphite powder is less than 500μm; the mixed smelting is non-sealed smelting, and the rotation speed of the mixed smelting is 60r / min~80r / min.
[0024] In S2 of the above preparation method, the mixed melting is carried out under the protection of an inert gas.
[0025] In S3 of the above preparation method, the melting is carried out under the protection of an inert gas.
[0026] In S4 of the above preparation method, an inert gas is introduced into the sealed furnace for protection; the stirring speed is 100 r / min to 200 r / min, and the stirring time is less than 15 min.
[0027] In S5 of the above preparation method, the coolant includes the following raw materials in mass percentage: 1% to 3% basalt fiber, 1% to 3% dispersant, 3% to 6% thickener, and the balance is water; the dispersant is sodium dodecylbenzene sulfonate, calcium lignin sulfonate or sodium lignin sulfonate; the thickener is sodium carboxymethyl cellulose or sodium polyacrylate; the diameter of the basalt fiber is less than 15 μm, and the length of the basalt fiber is 20 μm to 80 μm.
[0028] In S6 of the above preparation method, the qualified rate of the sorting is above 97.5%, and the unqualified semi-finished steel shots selected include hollow ball steel shots and irregular shaped steel shots, and the irregular shapes include polygonal, hemispherical and flat.
[0029] The vanadium-titanium-niobium composite steel shot is used as a metal abrasive, and the steel shot is blasted by a shot blasting machine or a sand blasting machine to clean and strengthen the metal surface.
[0030] The vanadium-titanium-niobium composite steel shot provided by the present invention and its preparation method and application have the following beneficial effects compared with the prior art:
[0031] 1. The steel shot of the present invention is a high-carbon alloy steel, and its ingredients contain vanadium, titanium, niobium, manganese, silicon, chromium, boron, basalt fiber, iron and other ingredients in specific proportions. The combined use of the ingredients can greatly improve the performance and corrosion resistance of the high-carbon steel shot, and comprehensively improve the hardness and toughness. After shot peening, the steel shot can maintain integrity during the cleaning and strengthening process, will not break easily, and has a small loss rate.
[0032] Vanadium has a strong affinity with carbon, nitrogen and oxygen, and will form corresponding stable compounds. It mainly exists in the form of carbides in steel. These carbides can hinder the growth of grains during solidification and heat treatment of steel, and refine the grains. Grain refinement can improve the strength and toughness of steel, because the increase in grain boundaries can hinder the movement of dislocations, making steel more difficult to deform; when vanadium is dissolved into solid solution at high temperature, it can increase the hardenability of steel, making it easier to obtain uniform martensitic structure during quenching, and improve the hardness and strength of steel; vanadium can increase the tempering stability of quenched steel, resist the reduction of hardness during tempering, and produce a secondary hardening effect, that is, after tempering, the hardness of steel will be further improved, improving the wear resistance and service life of steel shot.
[0033] Titanium has a strong affinity with nitrogen, oxygen, and carbon. It is a good deoxidizer and an effective element for fixing nitrogen and carbon. It can reduce the content of oxygen, nitrogen and other gases in steel, reduce the adverse effects of gases on steel performance, and improve the purity of steel. Titanium fixes nitrogen and sulfur and forms titanium carbide, which improves the strength of steel. After normalizing, the grains are refined and the precipitation of carbides can significantly improve the plasticity and impact toughness of steel. Titanium carbide has strong bonding, stability, and is not easy to decompose. Titanium carbide particles have the effect of preventing grain growth. Refining grains can also improve the strength and toughness of steel.
[0034] Part of the niobium in the high content is dissolved into the solid solution to strengthen the solid solution, and when it exists in the form of carbides and oxide particles, it can refine the grains. The refined grains can improve the strength and toughness of the steel, and reduce the overheating sensitivity and temper brittleness of the steel, making it easier to obtain a uniform structure during quenching, thereby improving the performance of the steel. Niobium can increase the tempering stability of the steel and has a secondary hardening effect, similar to the effect of vanadium, which can improve the hardness and wear resistance of the steel. The high content of niobium makes the steel have good hydrogen resistance.
[0035] Manganese can improve the strength and hardness of steel shot and improve the hot working performance of steel. Manganese can dissolve into ferrite and cementite, enhance the strength of ferrite and improve the hardness of cementite, thus improving the strength and hardness of steel as a whole. Manganese has a strong affinity with sulfur and can form compounds such as manganese sulfide with sulfur, reducing the free state of sulfur in steel, thereby reducing the brittle damage of sulfur to steel and improving the toughness and machinability of steel shot.
[0036] Carbon is one of the key elements that determine the hardness of steel shot. An appropriate amount of carbon can form cementite with iron to improve the hardness and strength of steel. However, if the carbon content is too high, the toughness of the steel shot will decrease and it will be easy to break; if the carbon content is too low, the hardness of the steel shot will be insufficient and it will not play the proper cleaning and strengthening role. Therefore, the present invention adds a relatively high content of vanadium, titanium, and niobium to combine with carbon to avoid free carbon from reducing the toughness of the steel shot and effectively reduce the shot peening breakage rate.
[0037] Silicon can deoxidize molten steel, reduce the oxygen content in steel, and improve the purity of steel. At the same time, silicon solid solution in steel can improve the strength of steel, especially the elastic limit, yield point and tensile strength. Silicon improves the fluidity of molten steel and is conducive to centrifugal atomization molding.
[0038] Chromium can increase the hardenability of steel and has a secondary hardening effect. It can improve the hardness and wear resistance of carbon steel without making the steel brittle. In steel shot, the presence of chromium can increase the surface hardness of the steel shot, enhance its wear resistance, and extend the service life of the steel shot. Chromium can form a dense oxide film on the surface of steel, improve the corrosion resistance of the steel shot, and enable it to maintain good performance in some harsh environments.
[0039] Adding a small amount of boron can improve the hardenability of steel, make it easier to obtain uniform structure during quenching, and improve the overall performance of steel shot.
[0040] Basalt fiber has high tensile strength and mechanical properties. When added to steel shot, it can enhance the strength and toughness of the steel shot and reduce the breakage and loss of the steel shot during use. Basalt fiber has good wear resistance and can improve the wear resistance of the steel shot, making it more effective in cleaning and strengthening the surface of the workpiece.
[0041] Vanadium, titanium and niobium all have the function of refining grains. When used together, they can further refine the grains of steel shots, making the organization of steel shots more uniform and dense, thereby improving the strength, toughness and wear resistance of steel shots. At the same time, they also have a synergistic effect in improving hardenability, tempering stability and secondary hardening, which can make steel shots have better performance after heat treatment. Manganese can improve the strength and hardness of steel, while silicon can improve the elastic limit and tensile strength of steel. The combined effect of the two can improve the comprehensive mechanical properties of steel shots. In addition, the deoxidation effect of silicon can reduce the oxygen content in steel, providing better conditions for the strengthening effect of manganese. Chromium can improve the hardness and corrosion resistance of steel, and boron can improve the hardenability of steel and improve the organization. The synergistic effect of the two can improve the hardness, wear resistance and uniformity of steel shots. Basalt fiber combines with the metal components in steel to give full play to their respective advantages. The metal components provide the basic strength and hardness of steel shots, while basalt fibers play an auxiliary role in strengthening, wear resistance and cost reduction, making the performance of steel shots more excellent.
[0042] 2. In the steel shot preparation method of the present invention, vanadium, chromium and boron are mixed and melted at 2100℃~2300℃, niobium is melted at 2500℃~2800℃, and the melted materials are mixed to prepare molten steel. Pre-melting can improve the fusion effect and form a more uniform crystal phase. Pre-melting can also save energy and effectively reduce the overall melting time of the sealed furnace.
[0043] 3. Conventional coolant is deionized water; the present invention designs a specific content of basalt fiber, dispersant, and thickener to be added to water to prepare the coolant. The dispersant helps to disperse the basalt fiber evenly in water; the thickener can improve the suspension of basalt fiber in the coolant, and the basalt fiber and thickener can increase the resistance of the coolant to the steel shot droplets, which can improve the quality of the steel shot molding morphology, making it more rounded and consistent, and effectively reduce the morphology failure rate. When basalt fiber is added to the coolant, it can adhere to and fuse on the surface of the steel shot droplets when the steel shot droplets enter the coolant, forming steel shots with basalt fibers attached to the surface, thereby improving the surface wear resistance of the steel shot and improving crack resistance. The viscosity resistance of the coolant can promote the fusion of basalt fiber. Basalt fiber has a low melting point. If it participates in smelting, the structure of basalt will be destroyed and the composition will be changed. The present invention is designed to add basalt fiber to the coolant. Basalt does not participate in smelting, which can protect the integrity of the fiber structure and composition, maximize the surface wear resistance and crack resistance, and protect the steel shot from corrosion.
[0044] Fourth, the method of the present invention designs the quenching temperature and tempering temperature according to the characteristics of the alloy to ensure the hardness and toughness of the steel shot product. In addition, quenching at 900℃~1000℃ can further improve the fusion of basalt fiber and steel shot, and further improve the toughness, wear resistance and crack resistance of the steel shot. DETAILED DESCRIPTION
[0045] The present invention is further described below in conjunction with specific implementation cases, but the present invention is not limited to these embodiments.
[0046] Example 1
[0047] A vanadium-titanium-niobium composite steel shot comprises the following components in percentage by mass: 1.24% vanadium, 1.20% titanium, 1.80% niobium, 1.35% manganese, 1.15% carbon, 0.82% silicon, 0.75% chromium, 0.50% boron, 0.30% basalt fiber, 0.02% sulfur, 0.03% phosphorus, and the balance is iron.
[0048] The method for preparing the above-mentioned vanadium-titanium-niobium composite steel shot comprises the following steps:
[0049] S1: Add titanium, manganese, carbon and silicon to molten iron at 1800°C according to mass percentage, and perform non-sealed mixed smelting at a speed of 70r / min to obtain fluid A;
[0050] S2: Mix and melt vanadium, chromium and boron at 2200°C under the protection of inert gas according to mass percentage to obtain fluid B;
[0051] S3: According to the mass percentage, under the protection of inert gas, niobium is melted at 2600°C to obtain fluid C;
[0052] S4: Fluid A, fluid B and fluid C are transferred into a sealed furnace, an inert gas is introduced into the sealed furnace for protection, the temperature is raised to 2500°C and stirred evenly at a stirring speed of 150r / min for 12min, and then the temperature is lowered to 1700°C to obtain molten steel;
[0053] S5: Use centrifugal atomization granulation equipment to sling the molten steel into small droplets, and throw the small droplets into the coolant, the coolant shapes the small droplets to obtain semi-finished steel shots;
[0054] The coolant includes the following raw materials in percentage by mass: 2% basalt fiber, 2% dispersant, 4.5% thickener, and the balance is water; wherein the dispersant is sodium dodecylbenzene sulfonate; the thickener is sodium carboxymethyl cellulose;
[0055] S6: taking out the semi-finished steel shots, washing, drying and sorting them, and then quenching the semi-finished steel shots that have passed the sorting, heating them to 950°C, keeping them warm for 25 minutes and then cooling them with water to obtain quenched steel shots;
[0056] S7: The quenched steel shot is tempered at 450°C for 65 minutes. After cooling, the particle size is finely screened to obtain finished steel shots with consistent size specifications.
[0057] Example 2
[0058] A vanadium-titanium-niobium composite steel shot comprises the following components in percentage by mass: 1.00% vanadium, 1.00% titanium, 1.50% niobium, 1.20% manganese, 0.90% carbon, 0.50% silicon, 0.50% chromium, 0.30% boron, 0.10% basalt fiber, 0.01% sulfur, 0.01% phosphorus, and the balance is iron.
[0059] The method for preparing the above-mentioned vanadium-titanium-niobium composite steel shot comprises the following steps:
[0060] S1: Add titanium, manganese, carbon and silicon to molten iron at 1700°C according to mass percentage, and perform non-sealed mixed smelting at a speed of 60r / min to obtain fluid A;
[0061] S2: Mix and melt vanadium, chromium and boron at 2100°C under the protection of inert gas according to mass percentage to obtain fluid B;
[0062] S3: According to the mass percentage, under the protection of inert gas, niobium is melted at 2500°C to obtain fluid C;
[0063] S4: Fluid A, fluid B and fluid C are transferred into a sealed furnace, an inert gas is introduced into the sealed furnace for protection, the temperature is raised to 2480°C and stirred evenly at a stirring speed of 100 r / min for 8 minutes, and then the temperature is lowered to 1600°C to obtain molten steel;
[0064] S5: Use centrifugal atomization granulation equipment to sling the molten steel into small droplets, and throw the small droplets into the coolant, the coolant shapes the small droplets to obtain semi-finished steel shots;
[0065] The coolant includes the following raw materials in percentage by weight: 1% basalt fiber, 1% dispersant, 3% thickener, and the balance is water; wherein the dispersant is calcium lignin sulfonate; the thickener is sodium carboxymethyl cellulose;
[0066] S6: taking out the semi-finished steel shots, washing, drying and sorting them, and then quenching the semi-finished steel shots that have passed the sorting, heating them to 900°C, keeping them warm for 20 minutes and then cooling them with water to obtain quenched steel shots;
[0067] S7: The quenched steel shot is tempered and kept at 400°C for 50 minutes. After cooling, the particle size is finely screened to obtain finished steel shots with consistent size specifications.
[0068] Example 3
[0069] A vanadium-titanium-niobium composite steel shot comprises the following components in percentage by mass: 1.15% vanadium, 1.18% titanium, 1.64% niobium, 1.25% manganese, 1.05% carbon, 0.65% silicon, 0.73% chromium, 0.46% boron, 0.28% basalt fiber, 0.25% sulfur, 0.32% phosphorus, and the balance is iron.
[0070] The method for preparing the above-mentioned vanadium-titanium-niobium composite steel shot comprises the following steps:
[0071] S1: Add titanium, manganese, carbon and silicon to molten iron at 1750°C according to mass percentage, and perform non-sealed mixed smelting at a speed of 65r / min to obtain fluid A;
[0072] S2: Mix and melt vanadium, chromium and boron at 2150°C under the protection of inert gas according to mass percentage to obtain fluid B;
[0073] S3: According to the mass percentage, under the protection of inert gas, niobium is melted at 2550°C to obtain fluid C;
[0074] S4: fluid A, fluid B and fluid C are transferred into a sealed furnace, an inert gas is introduced into the sealed furnace for protection, the temperature is raised to 2500°C and stirred evenly at a stirring speed of 120r / min for 10min, and then the temperature is lowered to 1650°C to obtain molten steel;
[0075] S5: Use centrifugal atomization granulation equipment to sling the molten steel into small droplets, and throw the small droplets into the coolant, the coolant shapes the small droplets to obtain semi-finished steel shots;
[0076] The coolant includes the following raw materials in percentage by weight: 1.5% basalt fiber, 1.5% dispersant, 3.5% thickener, and the balance is water; wherein the dispersant is sodium lignin sulfonate; the thickener is sodium carboxymethyl cellulose;
[0077] S6: taking out the semi-finished steel shots, washing, drying and sorting them, and then quenching the semi-finished steel shots that have passed the sorting, heating them to 930°C, keeping them warm for 22 minutes and then cooling them with water to obtain quenched steel shots;
[0078] S7: The quenched steel shot is tempered and kept at 420°C for 60 minutes. After cooling, the particle size is finely screened to obtain finished steel shots with consistent size specifications.
[0079] Example 4
[0080] A vanadium-titanium-niobium composite steel shot comprises the following components in percentage by mass: 1.40% vanadium, 1.45% titanium, 1.90% niobium, 1.45% manganese, 1.20% carbon, 0.95% silicon, 0.90% chromium, 0.50% boron, 0.42% basalt fiber, 0.04% sulfur, 0.03% phosphorus, and the balance is iron.
[0081] The method for preparing the above-mentioned vanadium-titanium-niobium composite steel shot comprises the following steps:
[0082] S1: Add titanium, manganese, carbon and silicon to molten iron at 1850°C according to mass percentage, and perform non-sealed mixed smelting at a speed of 75r / min to obtain fluid A;
[0083] S2: Mix and melt vanadium, chromium and boron at 2250°C under the protection of inert gas according to mass percentage to obtain fluid B;
[0084] S3: According to the mass percentage, under the protection of inert gas, niobium is melted at 2700°C to obtain fluid C;
[0085] S4: fluid A, fluid B and fluid C are transferred into a sealed furnace, an inert gas is introduced into the sealed furnace for protection, the temperature is raised to 2550°C and stirred evenly at a stirring speed of 180r / min for 14min, and then the temperature is lowered to 1750°C to obtain molten steel;
[0086] S5: Use centrifugal atomization granulation equipment to sling the molten steel into small droplets, and throw the small droplets into the coolant, the coolant shapes the small droplets to obtain semi-finished steel shots;
[0087] The coolant includes the following raw materials in percentage by weight: 2.5% basalt fiber, 2.8% dispersant, 5% thickener, and the balance is water; wherein the dispersant is sodium dodecylbenzene sulfonate; the thickener is sodium polyacrylate;
[0088] S6: taking out the semi-finished steel shot, washing, drying and sorting, and then quenching the semi-finished steel shot that has passed the sorting, heating it to 980°C, keeping it warm for 28 minutes and then cooling it with water to obtain quenched steel shot;
[0089] S7: The quenched steel shot is tempered at 480°C for 70 minutes. After cooling, the particle size is finely screened to obtain finished steel shots with consistent size specifications.
[0090] Example 5
[0091] A vanadium-titanium-niobium composite steel shot comprises the following components in percentage by mass: 1.50% vanadium, 1.50% titanium, 2.00% niobium, 1.50% manganese, 1.30% carbon, 1.00% silicon, 1.00% chromium, 0.60% boron, 0.50% basalt fiber, 0.05% sulfur, 0.05% phosphorus, and the balance is iron.
[0092] The method for preparing the above-mentioned vanadium-titanium-niobium composite steel shot comprises the following steps:
[0093] S1: Add titanium, manganese, carbon and silicon to molten iron at 1900°C according to mass percentage, and perform non-sealed mixed smelting at a speed of 80r / min to obtain fluid A;
[0094] S2: Mix and melt vanadium, chromium and boron at 2300°C under the protection of inert gas according to mass percentage to obtain fluid B;
[0095] S3: According to the mass percentage, under the protection of inert gas, niobium is melted at 2800°C to obtain fluid C;
[0096] S4: fluid A, fluid B and fluid C are transferred into a sealed furnace, an inert gas is introduced into the sealed furnace for protection, the temperature is raised to 2600°C and stirred evenly at a stirring speed of 200r / min for 15min, and then the temperature is lowered to 1800°C to obtain molten steel;
[0097] S5: Use centrifugal atomization granulation equipment to sling the molten steel into small droplets, and throw the small droplets into the coolant, the coolant shapes the small droplets to obtain semi-finished steel shots;
[0098] The coolant includes the following raw materials in percentage by mass: 3% basalt fiber, 3% dispersant, 6% thickener, and the balance is water; wherein the dispersant is calcium lignin sulfonate; the thickener is sodium polyacrylate;
[0099] S6: taking out the semi-finished steel shots, washing, drying and sorting them, and then quenching the semi-finished steel shots that have passed the sorting, heating them to 1000°C, keeping them warm for 30 minutes and then cooling them with water to obtain quenched steel shots;
[0100] S7: The quenched steel shot is tempered at 500°C for 80 minutes. After cooling, the particle size is finely screened to obtain finished steel shot with consistent size specifications.
[0101] The molten iron used in the above embodiments is molten iron obtained by smelting and removing impurities from iron ore, and the molten iron contains impurities of sulfur <0.05% and phosphorus <0.05%; the carbon used is graphite powder, and the particle size range of the graphite powder is below 500μm; the inert gas used is nitrogen; the diameter range of the basalt fiber used is below 15μm, and the length range of the basalt fiber is 20μm to 80μm.
[0102] The preparation methods of the above-mentioned embodiments can select centrifugal atomization granulation equipment with different granulation apertures and particle size fine screens according to the needs of product use, and prepare finished steel shots with different diameters of 0.2mm to 3.0mm. The diameter specifications are divided into: 0.2mm, 0.3mm, 0.5mm, 0.6mm, 0.8mm, 1.0mm, 1.2mm, 1.4mm, 1.7mm, 2.0mm, 2.5mm, 3.0mm. The sorting qualified rate of semi-finished steel shots of various diameter specifications is above 97.5%, and the unqualified semi-finished steel shots selected include hollow ball steel shots and irregular shaped steel shots. The irregular shapes include polygonal, hemispherical and flat shapes. The density of the finished steel shots of various diameter specifications is greater than 7.40g / cm 3 .
[0103] The steel shots prepared in the above-mentioned embodiments are used as metal abrasives. The steel shots are blasted by a shot blasting machine or a sand blasting machine to clean and strengthen the metal surface.
[0104] Comparative Example 1
[0105] The steel shot composition includes: titanium 0.50%, niobium 0.70%; other parameters and methods are the same as in Example 1.
[0106] Comparative Example 2
[0107] The steel shot composition includes: 0.50% vanadium, 0.30% chromium, and 0.15% boron; other parameters and methods are the same as in Example 1.
[0108] Comparative Example 3
[0109] The steel shot components include: 0.50% titanium, 0.70% niobium, 0.50% vanadium, 0.30% chromium, and 0.15% boron; other parameters and methods are the same as those in Example 1.
[0110] Comparative Example 4
[0111] The components in S1, S2 and S3 are not melted separately; that is, S1: titanium, manganese, carbon, silicon, vanadium, chromium, boron and niobium are added to molten iron at 1800°C in percentage by mass, and non-sealed mixed smelting is carried out at a speed of 70r / min to obtain fluid A; S2 and S3 are omitted; in S4, fluid A is transferred to a sealed furnace, an inert gas is introduced into the sealed furnace for protection, the temperature is raised to 2500°C and stirred evenly, the stirring speed is 150r / min, the stirring time is 12min, and then the temperature is lowered to 1700°C to obtain molten steel; other parameters and methods are the same as those in Example 1.
[0112] Comparative Example 5
[0113] In S5, water is used as the coolant; other parameters and methods are the same as those in Example 1.
[0114] Comparative Example 6
[0115] In S5, no thickener is added to the coolant; other parameters and methods are the same as in Example 1.
[0116] Comparative Example 7
[0117] In S6, the heating temperature of the quenching treatment is 700°C; other parameters and methods are the same as in Example 1.
[0118] Comparative Example 8
[0119] The steel shot contains: 0.50% titanium, 0.70% niobium, 0.50% vanadium, 0.30% chromium and 0.15% boron; water is used as the coolant; the heating temperature of the quenching treatment is 700° C.; other parameters and methods are the same as those in Example 1.
[0120] The steel shots with a diameter of 0.6 mm prepared in the above-mentioned embodiments and comparative examples were taken for parallel index testing.
[0121] (1) Hardness test: The steel shot is placed on a Rockwell hardness tester calibrated with a standard hardness block to measure the hardness. Ten steel shots are taken from each group and measured three times in parallel. The results are averaged. The test calculation results are shown in Table 1 below.
[0122] (2) Density test: The density of steel shot was tested using a bulk density tester. The test results are shown in Table 1 below.
[0123] (3) Deformation and crushing rate test: 10 kg of steel shot was taken from each group, and 3 mm thick Q235 steel was shot peened three times at a shot peening speed of 100 m / s. After shot peening, steel shots that met the standards (no crushing, no deformation) were selected, and the weight of steel shots that met the standards was weighed to calculate the deformation and crushing rate. Deformation and crushing rate = (weight of steel shot before shot peening - weight of steel shot that still met the standards after shot peening three times) / weight of steel shot before shot peening × 100%. The test calculation results are shown in Table 1 below.
[0124] (4) Anti-corrosion test: 1 kg of steel shot was taken from each group and placed on the sample rack of the salt spray test chamber. A neutral salt spray test (sodium chloride solution concentration of 5%, test temperature of 35±2℃, salt spray deposition rate of 1.5 ml / 80 cm² / h) was performed and the spraying was continued for 150 h. The steel shot was taken out, cleaned, dried and weighed again to calculate the mass loss rate. The test calculation results are shown in Table 1 below.
[0125] It can be seen from the above results that the steel shots of Examples 1 to 5 have good hardness and density, and the deformation and breakage rate after use is low. After shot peening, the steel shots can maintain integrity during the cleaning and strengthening process and will not break easily; the corrosion resistance is good. From the results of Comparative Examples 1 to 2, it can be seen that by reducing the content of titanium, niobium or vanadium, chromium, and boron in the components, the hardness and density of the steel shots do not fluctuate much, but the deformation and breakage rate and corrosion quality loss rate of shot peening are improved; from the results of Comparative Example 3, it can be seen that by reducing the content of titanium, niobium, vanadium, chromium, and boron in the components at the same time, the deformation and breakage rate and corrosion quality loss rate of shot peening are significantly improved. From the results of Comparative Example 4, it can be seen that the components in S1, S2, and S3 are not melted separately, which affects the preparation quality of the steel shots, the homogeneity is poor, and it is easier to deform and break after shot peening. From the results of Comparative Example 5, it can be seen that only water is used as a coolant, the basalt fiber component is missing from the surface of the steel shots, and it is easier to deform and break after shot peening. From the results of comparative example 6, it can be seen that not adding thickener to the coolant mainly affects the preparation morphology of the steel shot. The morphology of the steel shot is not standardized, and it is easy to be unevenly stressed after shot peening, and it is easy to break and deform. From the results of comparative example 7, it can be seen that in S6, the heating temperature of the quenching treatment is reduced to 700°C, the hardness and density of the composite steel shot are reduced, and it is easy to deform and break after shot peening, and the corrosion resistance is poor. From the results of comparative example 8, it can be seen that by reducing the content of titanium, niobium, vanadium, chromium, and boron in the components at the same time, using only water as the coolant, and reducing the heating temperature of the quenching treatment to 700°C, the performance of the prepared steel shot is deteriorated, the deformation and breakage rate is significantly improved, which seriously affects the ability of the steel shot to maintain integrity during the cleaning and strengthening process; and the corrosion resistance is deteriorated.
Claims
1. A vanadium-titanium-niobium composite steel shot, characterized in that: The steel shot includes the following components in mass percentage: vanadium 1.00% ~ 1.50%, titanium 1.00% ~ 1.50%, niobium 1.50% ~ 2.00%, manganese 1.20% ~ 1.50%, carbon 0.90% ~ 1.30%, silicon 0.50% ~ 1.00%, chromium 0.50% ~ 1.00%, boron 0.30% ~ 0.60%, basalt fiber 0.10% ~ 0.50%, sulfur < 0.05%, phosphorus < 0.05%, and the balance is iron; The preparation method of the steel shot comprises the following steps: S1: Add titanium, manganese, carbon and silicon to molten iron at 1700℃~1900℃ according to mass percentage, mix and smelt evenly to obtain fluid A; S2: Mix and melt vanadium, chromium and boron at 2100°C to 2300°C according to mass percentage to obtain fluid B; S3: melting niobium at 2500°C to 2800°C according to mass percentage to obtain fluid C; S4: fluid A, fluid B and fluid C are transferred into a sealed furnace, heated to 2480°C to 2600°C and stirred evenly, and then cooled to 1600°C to 1800°C to obtain molten steel; S5: Use centrifugal atomization granulation equipment to sling the molten steel into small droplets, and throw the small droplets into the coolant, the coolant shapes the small droplets to obtain semi-finished steel shots; The coolant includes the following raw materials in percentage by mass: 1% to 3% basalt fiber, 1% to 3% dispersant and 3% to 6% thickener, and the balance is water; S6: taking out the semi-finished steel shot, washing, drying and sorting, and then quenching the semi-finished steel shot that has passed the sorting, heating it to 900°C to 1000°C, keeping it warm for 20min to 30min, and then water cooling it to obtain quenched steel shot; S7: Temper the quenched steel shot, keep it at 400℃~500℃ for 50min~80min, cool it down, and finely screen the particle size to obtain finished steel shot with consistent size specifications.
2. The vanadium-titanium-niobium composite steel shot according to claim 1, characterized in that: The density of the steel shot is greater than 7.40 g / cm 3 ; The diameter specification of the steel shot is 0.2mm~3.0mm.
3. A method for preparing a vanadium-titanium-niobium composite steel shot, used for preparing the vanadium-titanium-niobium composite steel shot according to claim 1, characterized in that: The preparation method comprises the following steps: S1: Add titanium, manganese, carbon and silicon to molten iron at 1700℃~1900℃ according to mass percentage, mix and smelt evenly to obtain fluid A; S2: Mix and melt vanadium, chromium and boron at 2100°C to 2300°C according to mass percentage to obtain fluid B; S3: melting niobium at 2500°C to 2800°C according to mass percentage to obtain fluid C; S4: fluid A, fluid B and fluid C are transferred into a sealed furnace, heated to 2480°C to 2600°C and stirred evenly, and then cooled to 1600°C to 1800°C to obtain molten steel; S5: Use centrifugal atomization granulation equipment to sling the molten steel into small droplets, and throw the small droplets into the coolant, the coolant shapes the small droplets to obtain semi-finished steel shots; The coolant includes the following raw materials in percentage by mass: 1% to 3% basalt fiber, 1% to 3% dispersant and 3% to 6% thickener, and the balance is water; S6: taking out the semi-finished steel shot, washing, drying and sorting, and then quenching the semi-finished steel shot that has passed the sorting, heating it to 900°C to 1000°C, keeping it warm for 20min to 30min, and then water cooling it to obtain quenched steel shot; S7: Temper the quenched steel shot, keep it at 400℃~500℃ for 50min~80min, cool it down, and finely screen the particle size to obtain finished steel shot with consistent size specifications.
4. The method for preparing a vanadium-titanium-niobium composite steel shot according to claim 3, characterized in that: In S1, the molten iron is molten iron obtained by smelting and removing impurities from iron ore, and the molten iron contains impurities of sulfur <0.05% and phosphorus <0.05%; the carbon is graphite powder, and the particle size of the graphite powder is less than 500μm; the mixed smelting is non-sealed smelting, and the rotation speed of the mixed smelting is 60r / min~80r / min.
5. The method for preparing vanadium-titanium-niobium composite steel shot according to claim 3, characterized in that: In S2, the mixed melting is carried out under the protection of an inert gas.
6. The method for preparing vanadium-titanium-niobium composite steel shot according to claim 3, characterized in that: In S3, the melting is carried out under the protection of an inert gas.
7. The method for preparing vanadium-titanium-niobium composite steel shot according to claim 3, characterized in that: In S4, an inert gas is introduced into the sealed furnace for protection; the stirring speed is 100 r / min to 200 r / min, and the stirring time is less than 15 min.
8. The method for preparing vanadium-titanium-niobium composite steel shot according to claim 3, characterized in that: In S5, the dispersant is sodium dodecylbenzene sulfonate, calcium lignin sulfonate or sodium lignin sulfonate; the thickener is sodium carboxymethyl cellulose or sodium polyacrylate; the diameter of the basalt fiber is less than 15 μm, and the length of the basalt fiber is 20 μm to 80 μm.
9. The method for preparing vanadium-titanium-niobium composite steel shot according to claim 3, characterized in that: In S6, the pass rate of the separation is above 97.5%.
10. The use of the vanadium-titanium-niobium composite steel shot according to claim 1, characterized in that: Steel shot is used as metal abrasive. It is blasted by shot blasting machine or sand blasting machine to clean and strengthen the metal surface.
Citation Information
Patent Citations
High-speed steel drilling bit for mine drilling rig and heat treatment method thereof
CN108504954A
Aluminum-based alloy product and preparation method thereof
CN114107845A